Implementasi Algoritma Correlation Tracker Untuk Sistem Pencarian Objek Menggunakan Library DLIB - Fajar Baskoro Ag (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
Object tracking is a process to determine and follow the position of a desired moving object using a camera in real time. There are various algorithms in making object tracking systems, one of which is the correlation tracker algorithm in the DLIB library. This object tracking system uses Raspberry Pi 4 which contains a python program for object tracking. Pi Camera is used as a realtime video image input. The results of using the correlation tracker algorithm in the DLIB library, namely the object tracking process can run well. There are 5 objects that are tracked and as a result the tracking box is always around the object, whether the object is moving left, right, forward, and backward. As the object moves back and forth, the scale on the tracking box may change according to the object's size. Performance on the Raspberry Pi can be seen from the video framerate of 10.5 fps.